Navigating Turnitin’s Limitations: Ph.D. Students’ Perceptions and Departmental Strategies for Academic Integrity at the University of Ibadan - ILORI, Kikelomo Margaret (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This study examines Ph.D. students’ perceptions of Turnitin’s effectiveness in detecting plagiarism and the departmental strategies used to address its limitations at the University of Ibadan. The focus is on disciplines that face technical writing challenges, namely English, History, Law, Cultural and Media Studies, and Gender Studies. Anchored in Protection Motivation Theory (PMT), the study employed semi-structured interviews with fifteen Ph.D. students drawn from the Faculty of Arts (five from English and five from History), the Faculty of Law (two students), and the Institute of African Studies (two from Cultural and Media Studies and one from Gender Studies). Data were analysed using thematic analysis. The findings reveal two major themes: students’ perceptions of Turnitin’s utility and limitations, and departmental adaptive strategies. While participants acknowledged Turnitin’s usefulness in promoting academic integrity, they expressed concerns about its high rate of false positives, particularly in legal citations, and its limited capacity to detect non-English and archival sources. These challenges contributed to low response efficacy and high response costs, including extensive citation reformatting. In response, departments adopted adaptive measures such as post-field seminars, pre-submission Turnitin checks, paraphrasing guidance, and supervisory support. These strategies reflect high response efficacy and self-efficacy within the PMT framework. However, their largely informal implementation highlights the absence of institutional standardisation. The study recommends the development of formal, discipline-sensitive plagiarism policies, including the establishment of a departmental or university-wide plagiarism review committee and customised Turnitin settings for specific disciplines. Training for supervisors and postgraduate students on interpreting similarity reports is also advised. Such measures would strengthen academic integrity, reduce inequities in thesis evaluation, and improve the effectiveness of plagiarism detection across diverse academic fields.